DISIPLIN GURU SEBAGAI PEGAWAI NEGERI SIPIL DI SEKOLAH MENENGAH KEJURUAN NEGERI 1 BANTAENG - Fatmawada S (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2018)
This research aims to find out the teachers discipline intensity at Vocational High School 1 Bantaeng.      This research conducted Descriptive Quantitative Method. The population of this research was all teacher which are civil servant at Vocational High School 1 Bantaeng furthermore, the sample of this research consisted of 80 teacher. In collecting the data, the researcher used some instruments, they are observation, questionnaire, and documentation. Furthermore, The researcher analyzed the data byconducting descriptive analysis using persetage (%) formula.    The result of this research showed that the intensity of the teachers discipline was high, which means the teacher showed the attitude of obedience both of doing their duty and following the applied regulations which relate with the indicators : time discripline, work discipline and discipline of using the school facilities Key words : Discipline, Teacher, Vocatioral High School 1 Bantaeng